Analysis of clinical characteristics and risk factors of infectious mononucleosis in children with splenomegaly - Gao, YaSong; Hu, FangQi (Frontiers in Pediatrics, 2025)
BackgroundThe initial Epstein–Barr virus infection in children often presents as infectious mononucleosis (IM). However, the risk factors for splenomegaly in IM remain unclear. This study investigated the clinical features and risk factors for splenomegaly in children with IM.MethodsThis retrospective study enrolled children diagnosed with IM between 2019 and 2024. Participants were divided into splenomegaly and non-splenomegaly groups. The relevant clinical data and laboratory examination results of the two groups were compared. Furthermore, multivariate logistic regression and receiver operating characteristic (ROC) curve analyses were performed on the relevant variables.ResultsSplenomegaly, a common clinical manifestation, was observed in 43.6% of the 179 children with IM. The splenomegaly group exhibited higher serum levels of alanine aminotransferase, r-glutamyl transpeptidase, and lactate dehydrogenase, along with higher rates of hepatomegaly and eyelid edema (P < 0.05). Multivariate analysis identified older age [odds ratio (OR) = 1.333], eyelid edema (OR = 3.242), and hepatomegaly (OR = 22.072) as independent risk factors (P < 0.05). ROC curve analysis determined 3.5 years as the optimal cut-off age for predicting splenomegaly.ConclusionsOlder age, hepatomegaly, and eyelid edema are risk factors for splenomegaly in children with IM, with the risk increasing beyond the cut-off age of 3.5 years. These findings provide clinicians with a practical tool to identify children at higher risk and to offer advice on limiting activities to avoid potential complications, especially in settings where advanced imaging is not readily available.